Iron Fist : Classic Armoured Warfare Case Studies - Perrett, Bryan (London Brockhampton Press, 1999)
The mechanical monsters of the 20th century provided new dramas of fircpower and impact in warfare. With the invention of the internal combustion engine, land warfare changed at an unprecedented pace. Strategies were revised, lactics which matched the new mobility were developed and both offensive drives and planned retreats could be executed with speed and precision. Selecting examples of armoured vehicle warfare action from the two world wars, the Middle East, Vietnam and the Gulf, the author uses both his professional knowledge and descriptive skills to recreate he atmosphere of the battlefield in the era of the tank whilst telling the story of the evolution of mechanised armour.
Include Maps, Colour Illustration, Bibliography and Index
Keywords: Tank warfare -- Military history, Modern -- Tanks (Military science) -- Battles